IMPROVING THE STUDENTS' PRONUNCIATION USING ENGLISH LANGUAGE SPEECH ASSISTANT (ELSA) APPLICATION (A PRE-EXPERIMENTAL RESEARCH AT THE ELEVENTH GRADE STUDENTS OF SMAN 9 MAKASSAR) - Muamar Muamar; Hj. Andi Tenri Ampa; St. Asmayanti AM (Journal of Language Testing and Assessment, 2022)
This study aims to improve the students pronunciation using English Language Speech Assistant (ELSA) application. this research used pre-experimental research by quantitative method. There were 36 students of SMA Negeri 9 Makassar involved in this research. the test was pronounce word which consist of 40 words for pre-test and post-test.The findings of the study indicated that the English Language Speech Assistant (ELSA) application is significant in improving students' pronunciation. This was proven by the average score pre-test before treatment was 51.94 and the average score after Treatment has given was 63.47, the percentage of the improvement was 22.19%. This means that there is improvement of students' pronunciation.